KORUPSI MELALUI JUAL BELI JABATAN DI PEMERINTAH DAERAH DALAM PERSPEKTIF SOSIOLOGI - Sugeng Pujileksono (Universitas Wijaya Kusuma Surabaya, 2022)
The sale and purchase of positions as a form of corruption in the selection process for local government positions in Indonesia is a violation of law and public morals. Corruption is a complex social phenomenon that requires an objective study and can be studied from various fields, one of which is sociology. This study aims to explain the sociological perspective on buying and selling positions as a form of corruption in local government. The method of this study is a literature study with seven steps based on the Cornell University model. This study helps to understand corruption through selling and purchasing positions from a sociological perspective. So far, corruption studies have been mostly from a legal and political perspective. Based on the study conducted, there are three theories to explain this reality, namely social exchange theory, rational choice theory, and Weber's theory of bureaucracy. Social exchange theory sees the phenomenon of corruption as a form of the exchange relationship between actors involved in buying and selling positions that tend to be corrupt. The rational choice theory sees the buying and selling of positions and corruption as models of human behavior are the results of the selfish preferences of individuals. Weber's model explains the sale and purchase of positions and corruption as a form of deviation from public officials in the legal-rational system (bureaucracy). Based on the explanations of the three theories, the sociological explanation of corruption through the sale and purchase of positions in local government may contradict the legal and political explanations.Keywords: Corruption, Buying And Selling Positions, Sociology Perspective